2019
DOI: 10.1111/ssm.12330
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an out‐of‐school STEM education program on students’ attitudes toward STEM and STEM careers

Abstract: There is an increasing awareness of out-of-school program value in enhancing student interest and understanding of science, technology, engineering, and mathematics (STEM). This study examined the impact of an out-of-school STEM education program on student attitudes toward STEM disciplines and STEM careers. A STEM education program implemented at a public research university was designed to integrate STEM disciplines with hands-on problem-based activities. Design features included authentic learning contexts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 23 publications
2
56
0
2
Order By: Relevance
“…The results of the research showed also that the integration of STEM activities into the out-of-school education programs could support the development of students' interest in STEM-related careers. Likewise, Baran, Canbazoglu Bilici, Mesutoglu, and Ocak (2019) and Guzey, Tank, Wang, Roehrig, and Moore (2014) stated that STEM training programs are important in improving student attitudes towards STEM. Duran and Sendag (2012) indicated that technology/inquiry and design-based collaborative learning strategies and technologysupported IT/STEM experiences have a significant effect on the development of critical thinking of urban high school students.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the research showed also that the integration of STEM activities into the out-of-school education programs could support the development of students' interest in STEM-related careers. Likewise, Baran, Canbazoglu Bilici, Mesutoglu, and Ocak (2019) and Guzey, Tank, Wang, Roehrig, and Moore (2014) stated that STEM training programs are important in improving student attitudes towards STEM. Duran and Sendag (2012) indicated that technology/inquiry and design-based collaborative learning strategies and technologysupported IT/STEM experiences have a significant effect on the development of critical thinking of urban high school students.…”
Section: Discussionmentioning
confidence: 99%
“…STEM education has merit in equipping students with engineering habits of mind, helping students produce multiple innovative solutions to 21 st -century problems, think creatively, and systematically (Akgunduz, 2018;Bybee, 2018;Corlu et al, 2014;Johnson et al, 2015, NRC, 2014. STEM education contributes to the development of students' problem-solving skills, abilities to engage in evidence-based explanations (Bybee, 2018), innovation capacities, collaboration, critical thinking (Martín-Páez et al, 2019, NRC, 2012, and interest towards STEM and STEM careers (Akgunduz, 2016;Baran et al, 2019;Martín-Páez et al, 2019;Shahali et al, 2017).…”
Section: Stem Educationmentioning
confidence: 99%
“…One example is that students whose science instruction integrated moral and ethical decisions, in line with SSI principles, showed gains in reflective writing (Zeidler et al., 2009). Further, students who engaged in engineering activities that incorporated science and math content within authentic contexts reported greater personal and societal relevance of STEM (Baran et al., 2019).…”
Section: Introductionmentioning
confidence: 99%